PENYELESAIAN SENGKETA DALAM UNDANG-UNDANG PERLINDUNGAN KONSUMEN DI INDONESIA - Andreawan, Yudo (Universitas Kapuas, 2025)
In recent years, there has been an encouraging increase in the attention paid by behavioral scientists to the legal system. A great deal—a great deal of jurisprudential thought—has been process-oriented. Theorists have done so with regard to the way decisions are made—whether precedent, race, education, social background, personality, or other factors influence judges toward one side or another in a particular controversy. Of course, scholars are very interested in the legal outcomes of these institutions, but they often limit the definition of output to outcomes or decisions and are not concerned with other types of decisions formal legal regulations output. Decisions (or outcomes) are unique applications of pre-existing rules. In resolving consumer disputes, the consumer's position is often a weak bargaining position. This means that consumers cannot exercise their rights in terms of evidence at trial. Even though the burden of proof is on the defendant, often in his decision the judge imposes the same burden of proof on the defendant. This is not in line with the legal nawacita made by the drafters of the consumer protection law, that consumers are the ones who occupy the highest position if a dispute occurs in court.